2020
DOI: 10.1017/s0144686x2000046x
|View full text |Cite
|
Sign up to set email alerts
|

Factors included in adult fall risk assessment tools (FRATs): a systematic review

Abstract: Falls often have severe financial and environmental consequences, not only for those who fall, but also for their families and society at large. Identifying fall risk in older adults can be of great use in preventing or reducing falls and fall risk, and preventative measures that are then introduced can help reduce the incidence and severity of falls in older adults. The overall aim of our systematic review was to provide an analysis of existing mechanisms and measures for evaluating fall risk in older adults.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…The ICF also offers a common terminology for the improvement of clinical and patient-orientated assessment instruments (Bickenbach et al 2012 ; World Health Organization 2012). A comparison between the perspectives of HCPs and a recent systematic review of FRATs (De Clercq et al 2020 ) indicated that the majority of perspectives of both the FRATS and the HCPs focussed on Body Function. It also showed that the knowledge of HCPs was in line with contemporary knowledge in the field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ICF also offers a common terminology for the improvement of clinical and patient-orientated assessment instruments (Bickenbach et al 2012 ; World Health Organization 2012). A comparison between the perspectives of HCPs and a recent systematic review of FRATs (De Clercq et al 2020 ) indicated that the majority of perspectives of both the FRATS and the HCPs focussed on Body Function. It also showed that the knowledge of HCPs was in line with contemporary knowledge in the field.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison between the clinical perspectives of HCPs on fall risk factors in older adults and the systematic review of FRATs (De Clercq et al 2020 ) revealed that the HCPs mentioned two relevant factors that were not captured in existing FRATs, namely ‘muscle-power functions’ and ‘mobility-of-joint functions’. Both of these ICF codes are important to consider for fall risk in older adults, as they relate directly to the ability to execute mobility activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous nursing assessments enables monitoring mobility issues that are frequently related to independence problems, falls, pressure sores, incontinence, and spasticity [ 10 , 11 ]. Standardized tools, such as the Conley Scale [ 12 ], the Morse Fall Scale [ 13 ], or the Tinetti Test [ 14 ], can be used to assess fall risk. The Barthel Test, a test of Activities of Daily Living (ADL) and the Instrumental Activities of Daily Living (IADL) test can be used to assess independence [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A framework such as the International Statistical Classification of Diseases and Related Health Problems (ICD), in contrast, focuses on classifying diseases and other health problems associated mainly with bodily disfunctions (World Health Organization [WHO], 2004). The ICF views functioning and disability as outcomes of interactions between the health condition (in this case, falls) and the contextual factors (in this case, fall risk factors), which include physical environmental risk factors such as natural or man-made products or environments (de Clercq et al, 2020). This framework has allowed us to code the older adult’s perception of fall risk factors into three categories, namely, (a) Body Function and Structure, (b) Activities and Participation, and (c) Environmental Factors.…”
Section: Introductionmentioning
confidence: 99%